Effect Of Weeding and Pest Control on Root Dynamics of Soybean (Glycine max (L.) Merril) on Sugarcane-Soybean Intercropping System - Iskandar Umarie; Wiwit Widiarti; Oktarina Oktarina; Ika Isnaini Rahayu; Muharromatul Hikmah (Universitas Muhammadiyah Jember, 2022)
Soybean (Glycine max (L.) Merill) is one of the important commodities in the provision of food, feed, and industrial materials, so it has become a major commodity in international trade. The need for global soybeans increases every year, along with population growth, improvement in per capita income, and the development of a food industry that is made from soybeans. This research was conducted in the experimental garden of the Faculty of Agriculture, Muhammadiyah University, Jember, Jember, East Java, Indonesia. The research was conducted in the form of factorial field experiments. The First Factor is F1: Weed Weeding Frequency, as many as 3 levels, yi: F1: Weeding once (15 hst), F2: Weeding 2 times (15, 30 hst), F3: Weeding 3 times (15, 30, and 45 days after) ) and and the second factor is Pest Control by 4 levels: I1 = Chemical Insecticide (Decis 25 EC), I2 = Vegetable Insecticide, I3 = Vegetable Insecticide Soursop Extract, I4 = Vegetable Insecticide of Neem Extract. The treatments above were arranged using a Complete Randomized Block Design (RCBD) which was repeated three times. The results of the study of weed frequency treatment significantly affected the growth of root nodules and the development of the roots of soybean plants. The best weed weeding frequency is weeding three times in one growing season. Treatment of pest control significantly affects the growth of root nodules and the development of the roots of soybean plants. The best pest control is pest control with chemical insecticides. The interaction of weed weeding frequency with pest control significantly influences the growth of root nodules and the root growth of soybean plants. The best interaction in this study is the interaction between the frequency of weeding three times sugar with pest control using chemical insecticides